CONCEPT OF MODERNITY: A COMPARATIVE ANALYSIS OF THE PERSPECTIVES OF GANDHI, NEHRU AND AMBEDKAR - Bhattacharya, Gangotri (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Modernity is a multifaceted concept that has evolved over time, encompassing various dimensions such as social, political, economic, and cultural transformations. In the Indian context, modernity emerged as a significant discourse during the late 19th and early 20th centuries, a period marked by colonial rule, social reform movements, and the struggle for independence. This article introduces the perspectives of three pivotal figures in Indian history—Mahatma Gandhi, Jawaharlal Nehru, and B.R. Ambedkar—each of whom articulated distinct visions of modernity that reflected their ideologies, experiences, and aspirations for the nation. By examining their views, one can gain insights into how modernity shaped individual identities and societal structures in India, particularly in contrast to medieval frameworks of authority and colonial legacy.